Pengaruh kepemilikan institusional, kepemilikan manajerial, komisaris independen, dan ukuran dewan komisaris terhadap manajemen laba serta implikasinya terhadap kinerja keuangan pada perusahaan manufaktur yang terdaftar di bursa efek indonesia periode 2012-2014 - Pricilia, Shierly; Susanto, Liana (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2017)
The purpose of this study is to analyze the effect of institusional ownership, managerial ownership, independent commissioner, and board of size on earning management and the implication on financial performance of manufacturing companies listed in the Indonesian Stock Exchange from 2012-2014. This research used the data of manufacturing companies that were selected using purposive sampling method for a total of 73 data in three years. Statistic method used in this study is multiple regression analysis and simple regression analysis. The data used in this research are secondary data in the form of financial statements that published during the observation year. The results of this study showed that earning management significantly affected by managerial ownership, and independent commissioner. Financial performance showed that significantly affected by earning management.